Sleep as a mediator between chronic diseases and depression: a NHANES study (2005–2018) - Tan, Ming; Zhao, Haihong; Nie, Ruya; Deng, Pingping; Wang, Cuixiao (Frontiers in Psychology, 2025)
ObjectiveThis article investigates the relationship between common chronic diseases and depression among US adults and examines the mediating role of sleep in this relationship, using a cross-sectional study to offer recommendations for depression prevention.MethodsThis study analyzed data from 10,710 participants collected from the National Health and Nutrition Examination Survey (NHANES) between 2005 and 2018. Logistic regression, subgroup analysis, restricted cubic spline (RCS) analysis, and mediation analysis were employed to explore the relationship between common chronic diseases and depression, and the mediating role of sleep.ResultsThe adjusted model indicated that stroke (OR = 1.712, 95% CI: 1.399, 2.103), heart disease (OR = 1.419, 95% CI: 1.262, 1.598), diabetes (OR = 1.243, 95% CI: 1.116, 1.386), and hypertension (OR = 1.249, 95% CI: 1.160, 1.346) were associated with an increased probability of depression. Additionally, trouble sleeping (OR = 2.059, 95% CI: 1.790, 2.375) was associated with an increased probability of depression, while sleep hours (OR = 0.867, 95% CI: 0.846, 0.888) may decrease this probability. RCS analysis showed a non-linear relationship between sleep hours and the risk of depression. The final mediation analysis showed that trouble sleeping mediated 3.66% of the effect of stroke, 12.68% of heart disease, and 17.76% of diabetes on depression. Furthermore, trouble sleeping mediated 11.07% of the impact of hypertension on depression, while sleep hours mediated 5.36% of this impact.ConclusionChronic diseases and sleep problems may increase the likelihood of depression among U.S. adults, with sleep serving as a mediator between chronic diseases and depression.